Knock induced erosion on Al pistons: Examination of damage morphology and its causes. (October 2018) - Balducci, E.; Ceschini, L.; Rojo, N.; Cavina, N.; Cevolani, R.; Barichello, M.
Abstract: In the present study, a systematic and deep examination of knocking damage on Al pistons is carried out, highlighting that only when exceeding a certain threshold knock compromises engine functionality. Controlled knocking combustions were induced during bench tests, by varying the spark advance for each cylinder. Several knock intensities and frequencies were investigated, with the aim to evaluate the possible knocking damages and to understand their influence on piston functionality. All the observed damages have been separately described and studied through failure analysis techniques, in particular optical and scanning electron microscopy and 3D digital microscopy, providing explanations of their occurrence. Among them, the erosion damage was predominantly observed and therefore fully evaluated. Preliminary attempts to relate engine parameters to knock damage were also made. This study is part of a wider project, whose aim is to increase knocking limits from the "safe calibration area" up to the limits which produce acceptable damages on pistons, in order to enhance engine efficiency. Graphical abstract: Unlabelled Image Highlights: Erosion knock damage develops through cracks nucleation and propagation in Al matrix, at the interface with Si particles. Erosion damage is well related to the severity of single knocking cycles (adequately represented by MAPO 99.5%). Piston valve reliefs are extremely sensitive to knock damage due to high surface/volume, which increases local temperature. Severe knock pressure oscillations can considerably damage the 1 st ring groove anodised layer, compromising its functionality. The instantaneous higher T due to knock produce alloy softening, acting as intensification factor of knock mechanical stress.